Social Assistance for FDIKOM UIN Jakarta Students for the Bintaro Scavenger Village Community - Tegar Pijar Matahari; Muhammad Rusydi Azmi; Wahyunengsih Wahyunengsih (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Social Assistance FDIKOM is a work program of DEMA FDIKOM which is an annual program. The 2022 FDIKOM Social Assistance Program will be held in Pemulung Village, Bintaro. The FDIKOM Social Assistance Program in 2022 is quite unique, because all of the actors or the implementing committee of the FDIKOM Social Assistance Program are new students (semester 1 students). FDIKOM Social Assistance has an interesting theme, namely, “SOLIDATE TOGETHER, BUILD BROTHERS, CREATE HAPPY”. The theme which contains the meaning of brotherhood among others is very related to the 2022 FDIKOM Social Assistance. FDIKOM Social Assistance is implemented to implement the Tri Dharma points of Higher Education, namely, Research, Education, and Community Service. Social assistance FDIKOM 2022 focuses on the third Tri Dharma point, namely Community Service. The purpose of implementing the 2022 FDIKOM Social Assistance Program is to increase our sense of concern among fellow human beings and also to help our brothers and sisters in Pemulung Village, either by providing basic food items, health checks and educational materials to local residents.